Communication in culturally diverse contexts - Perusset, Macarena (2023)
This paper addresses intercultural communication possibilities of a variety of care and health professionals in a private health organisation of Cordoba with a diverse patient population. The aim of this paper is to identify different elements present in an effective communication with those patients. Previous studies are considered to have overlooked this reality, even though it is of vital importance in communication between patients and health professionals, as it can result in misunderstandings, misdiagnosis and dissatisfaction with care on the one hand, and labor dissatisfaction on the other. In this study included the patients' own perceptions of their ability to communicate with the professionals. The participant observation technique was used during eight weeks and surveys were carried out with doctors from different specialties, nurses, as well as outpatients and inpatients at the institution. In the surveys, health professionals were asked to rate their ability to communicate with people from other cultures, and in the patient surveys, they were asked to rate the professionals' ability to communicate. Responses from 25 professionals (both doctors and nurses) and 91 patients were analysed. The results show that professionals with greater empathy and previous intercultural experience are more likely to communicate effectively with patients, in relation to their health care.